Digital Transformation in Maritime and City Logistics: Smart Solutions for Logistics - Carlos Jahn; Wolfgang Kersten; Christian M. Ringle (epubli GmbH, 2019)
This volume contains research contributions by an international group of authors addressing innovative and technology-based approaches for logistics and sustainability. They present simulation studies, systems and models for optimizations and digitalized solutions with a focus on maritime as well port and city logistics. This volume, edited by Carlos Jahn, Wolfgang Kersten, and Christian Ringle, provides valuable insights into digital transformation in logistics with regard to: Maritime and Port Logistics, City Logistics, Sustainability and Business Analytics.
urn:nbn:de:gbv:830-882.054033; https://econpapers.repec.org/RePEc:zbw:hiclch:209386; https://econpapers.repec.org/RePEc:zbw:hiclch:209387; https://econpapers.repec.org/RePEc:zbw:hiclch:209388; https://econpapers.repec.org/RePEc:zbw:hiclch:209389; https://econpapers.repec.org/RePEc:zbw:hiclch:209390; https://econpapers.repec.org/RePEc:zbw:hiclch:209391; https://econpapers.repec.org/RePEc:zbw:hiclch:209392; https://econpapers.repec.org/RePEc:zbw:hiclch:209393; https://econpapers.repec.org/RePEc:zbw:hiclch:209394; https://econpapers.repec.org/RePEc:zbw:hiclch:209395; https://econpapers.repec.org/RePEc:zbw:hiclch:209396; https://econpapers.repec.org/RePEc:zbw:hiclch:209397; https://econpapers.repec.org/RePEc:zbw:hiclch:209398; https://econpapers.repec.org/RePEc:zbw:hiclch:209399; https://econpapers.repec.org/RePEc:zbw:hiclch:209400
Keywords: 650; Logistics; Industry 4.0; Supply Chain Management; City Logistics; Sustainability; Maritime Logistics; Digitalization